Strategic Evaluation of the Traceless Staudinger Ligation for Radiolabeling with the Tricarbonyl Core - Constantin Mamat (MDPI AG, 2021)
The traceless Staudinger ligation with its two variants is a powerful biorthogonal conjugation method not only for the connection of biomolecules, but also for the introduction of fluorescence- or radiolabels under mild reaction conditions. Herein, the strategic evaluation of the traceless Staudinger ligation for radiolabeling 99mTc using the fac-[Tc(CO)3]+ core is presented. A convenient and high-yielding three-step synthetic procedure of dipicolylamine-based phosphanols as ligands for the mild radiolabeling was developed. The labeling was accomplished using a tricarbonyl kit and a 99mTc-pertechnetate generator eluate showing 87% radiochemical conversion. The respective rhenium-based, non-radioactive reference compounds were synthesized using (Et4N)2[Re(CO)3Br3] as precursor. All products were analyzed by NMR, MS, and elemental analysis. Additional XRD analyses were performed.